WORKING CAPITAL MANAGEMENT STRATEGY TO IMPROVE CASH CONVERSION CYCLE: CASE STUDY OF PT ABC - Maesaroh, Maya
Infrastructure is an important issue for economic growth in Indonesia. There are 13 types of infrastructure prioritized by presidential regulation and one of them is toll road infrastructure. It turns out that state-owned companies dominate toll road projects in Indonesia, and PT ABC is a supplier to these toll road projects and is engaged in construction. With the current case of default on maturing debt to SOE customers, it impacts the liquidity of the company. So this research is conducted with the aim of knowing the effect of customer default on Cash Conversion Cycle (CCC) and Net Working Capital (NWC) in the research period 2019 to Q3 2023. Then after analyzing each variable, the next step is to analyze the relationship between Cash Conversion Cycle (CCC) and Net Working Capital (NWC) using the Spearman's rho Correlation Test.